Does motor coordination influence perceptual-cognitive and physical factors of agility in young soccer players in a sport-specific agility task? - Menezes, G. B.; Oliveira, R. S.; Ferreira, A. B. M.; Assis, T. V. L.; Batista, E. S.; Oliver, J. L.; Lloyd, R. S.; Mortatti, A. L. (Sports Biomechanics, 2024)
This study aims to determine whether motor coordination influences the perception-decision time (perceptual-cognitive factor) and movement response time (physical factor) of young soccer players in a sport-specific agility task regardless of maturation. Eighty-seven young male soccer players were analysed. Anthropometric measurements were used to determine the maturity offset, while physical qualities including agility, change of direction speed (CODS) and motor coordination were also assessed. The following variables were obtained from these tests: Motor coordination score, perception-decision time, movement response time, agility time and CODS time. Motor coordination revealed a non-significant correlation with perception-decision time (r = 0.10, p = 0.34). However, motor coordination showed negative and significant correlations with CODS time (r = 0.47, p < 0.01), agility time (r = 0.52, p < 0.01) and movement response time (r = 0.62, p < 0.01). In addition, regression analysis showed that each increase in motor coordination score was associated with significant decreases in agility time (b = 0.023), movement response time (b = 0.021) and CODS time (b = 0.021) independent of maturity offset. The results of this study indicated that motor coordination was significantly related to the physical factors of agility in young soccer players.